KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PADA MASA PANDEMI COVID-19 - Zuul Fadhlil Adhiim; Fitri Nur Mahmudah (STKIP Pesisir Selatan, 2021)
The principal is the leader as well as the manager in the school. In any situation, the role of the principal is an important step to serve as a reference in developing competency and quality of education. This research was conducted with the aim of knowing the role of school principals in improving the quality of education during the Covid-19 pandemic. The method used is qualitative with a case study approach. This research setting was in MIS Babussalam, Nowa. Participants in this study were teachers who teach at MIS Babussalam, Nowa. Data collection techniques using structured interviews by arranging questions into interview guidelines. The research procedure used the Creswell case study approach. Data analysis was carried out with the assistance of the Atlas.ti software version 8. The results of this study indicate that the role of school principals in improving the quality of education during Covid-19 has the findings indicators are having a manner, being a manager, and being able to prioritize teachers and education personnel with HR development. The findings of this study can be recommended to all school principals as part of efforts to become school principals to optimize roles.